(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Antibiotic-resistant (AR) bacteria especially from commonly shared surfaces in the environment, pose a serious threat to global public health. The increasing demand for electronic banking and the associated risk of the spread of pathogenic bacteria makes it crucial to assess the antibiotic susceptibility and the presence of extended-spectrum beta-lactamase genes in bacteria isolated from automated teller machines (ATMs). Following standard procedures, a total of 22 samples were collected randomly from different ATMs using sterile cotton swabs soaked in physiologic saline and cultured on selective media. Isolates were characterized biochemically. Antibiotics susceptibility test was carried out on isolates using the Kirby-Bauer disc diffusion method. All Gram-negative isolates were subjected to polymerase chain reaction (PCR) to evaluate the common extended-spectrum beta-lactamase –encoding (ESBL) genes. Bacterial isolates were characterized as Klebsiella pneumoniae (33.33%), Pseudomonas aeruginosa (19.61%), Escherichia coli (15.69%), Staphylococcus aureus (9.80%), Acinetobacter spp. (7.84%), Enterobacter spp. and Bacillus subtilis (5.88%), and Enterococcus faecalis (1.96%). The highest antibiotic resistance pattern was displayed against ceftazidime (45.1%), followed by tetracycline (43.1%), cefixime (41.2%), ciprofloxacin and chloramphenicol (29.4%) and meropenem (9.8%). The TEM gene (54.8%) was recovered most, followed by CTX-M (28.6%) and SHV (19.0%). This study reveals that ATMs could harbour pathogenic bacteria with antibiotic resistance (AR) genes especially ESBL genes (blaTEM) which could be responsible for the widespread resistance to antibiotics. Therefore, adequate personal hygiene by users, proper cleaning regimen to sanitize these facilities regularly and public enlightenment are recommended to reduce the accompanying risks of spreading AR genes within the environment